INTERNATIONAL MARKET, ENTREPRENEURIAL AND LEARNING ORIENTATIONS AS DRIVERS OF FIRM PERFORMANCE - FEDER, Emőke–Szidónia (Studia Universitatis Babeș-Bolyai Oeconomica, 2015)
For contemporary firms, strategic orientations are indispensable resources of successful internationalisation, perceived as a high potential performance ensuring strategy. The foremost strategic choices studied within the resource-based perspective are the entrepreneurial, market and learning orientations. Therefore, the study aims to assess performance allegations of the above strategic orientation trinity integrated within the international business framework. Potential individual and multiple effects included in the universal configuration research model were explored on a survey based quantitative data collected from a sample of Romanian SMEs. Investigation findings revealed the positive individual influence of foreign market and international learning orientations. Further results highlighted a greater positive explanatory power of the synergistic strategic orientation triad on the international success. JEL Classification: L25, L26, M16